Transfection with CD40L induces tumour suppression by dendritic cell activation in an orthotopic mouse model of pancreatic adenocarcinoma. Issue 3 (3rd August 2007) - Serba, S; Schmidt, J; Wentzensen, N; Ryschich, E; Märten, A
Abstract : Objective: Patients with adenocarcinoma of the pancreas have only limited promising therapy options. Therefore, immunotherapeutic approaches might be considered promising and have gained importance over the last few years. In this study, CD40L gene transfer was tested as potent immunotherapy. Methods: The efficacy of CD40L gene transfer in initiating anti-tumour immune response was investigated in a pancreatic ductal adenocarcinoma orthotopic syngeneic mouse model. In addition, the role of dendritic cells was determined. Results: A significantly slower tumour growth rate and less metastasis were observed following administration of the CD40L plasmid. Such an effect of the plasmid was not observed in immunodeficient mice. Tumours of treated mice were found to be infiltrated with T cells and dendritic cells. The latter were mature and of myeloid origin. Tumour-infiltrating lymphocytes were tumour-specific as shown in IFN-γ ELISPot assays. Using intravital microscopy it was possible to show a significant induction of leukocytes sticking to the tumour endothelium after CD40L treatment. Adoptive cell transfer experiments have revealed that tumour-derived dendritic cells and CD8 cells from CD40L-treated donor mice either harbour anti-tumour activity or induce it in the recipients. Distinctly, CD8 cells from donor spleens were found to migrate directly into the recipient's tumour. Conclusions: The induction of anti-tumour activity initiated after treating mice with the CD40L plasmid was achieved. Further investigations showed that this is mediated by mature myeloid dendritic cells which activate CD8 cells. Clinical trials investigating CD40L-based therapies should be extended.